The EFFECT OF PHYSICAL ACTIVITY ON BLOOD SUGAR LEVELS IN DIABETES MELLITUS PATIENTS IN THE INTERNAL POLYCLINIC OF PINDAD HOSPITAL, BANDUNG - Sulistiyawati, Arie (Jurnal Kesehatan & Disiplin Ilmu, 2023)
Diabetes mellitus occurs due to increased glucose levels in the blood. Physical activity is any body movement produced by skeletal muscles that requires energy. Lack of physical activity is an independent risk factor for chronic disease. This study aims to determine the effect of physical activity on blood sugar levels in diabetes mellitus patients. This type of research is cross sectional, the sampling technique uses purposive sampling as many as 83 respondents. Data collection uses questionnaires and observation sheets. The results of research using the Wilcoxon test show that the p value of 0.000 is smaller than the alpha value (0.05), so it can be stated that Ho is rejected, which means that there is an influence of physical activity on blood sugar levels in diabetes mellitus patients at the internal medicine clinic at RSU Pindad Bandung. It is hoped that the results of this study can be used as a reference for interventions on types of physical activity to overcome blood sugar levels in diabetes mellitus patients.